Cooperative energy management of electrified vehicles on hilly roads. (April 2018) - Hovgard, Mattias; Jonsson, Oscar; Murgovski, Nikolce; Sanfridson, Martin; Fredriksson, Jonas
Abstract: This paper presents a control strategy and an assessment study for the potential of minimizing fuel consumption of electrified and/or conventional vehicles driving in a hilly terrain. The main idea is to minimize the amount of energy wasted on air resistance and mechanical braking. The former is achieved by having the vehicles drive close to each other. The latter is achieved by either allowing the speed to vary and thereby reduce braking, or by using the electric machine to brake and convert kinetic energy to electric energy that is stored in the battery. We propose a control strategy that is separated into two control layers. One layer optimizes vehicle velocity and battery state of charge using convex optimization, and the other optimizes gear and engine on/off state trajectories using dynamic programming. The control strategy is then applied to several test cases, in order to evaluate the reduction in fuel consumption due to platooning, optimal battery usage and optimal velocity control in a hilly terrain. Highlights: Cooperative adaptive cruise control of electrified vehicles. Platooning with electrified and conventional vehicles. Model-based predictive control of vehicles in a hilly terrain. Fuel efficient and safe cooperative energy management. Two-layer optimization with convex and dynamic programming.